2005
DOI: 10.1620/tjem.207.41
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Obstructive Pulmonary Disease in Japanese People on Medical Check-Up

Abstract: In Japan, spirometry has not been included as an item in medical check-ups for all persons. The purpose of this study was to show evidence to recommend spirometry routinely on medical check-up for the early detection of chronic obstructive pulmonary disease (COPD). There were 12,760 enrolled persons who underwent medical check-up. COPD was defined as a ratio of forced expiratory volume in one second to slow vital capacity of 70% or less. We investigated the prevalence and its characteristics of COPD in people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…We found that men presented a higher smoking prevalence rate, and this was slightly (1.1%) over the national level (52.0%) in 2001 4) . Takemura et al 31) reported a smoking rate of 49.5% in male clerical workers, which was lower than that in transport (64.5%) or production and labor (54.6%) related occupations. A similar finding was observed in the US population, with only 4.9% prevalence (the lowest) for office workers 32) .…”
Section: Discussionmentioning
confidence: 91%
“…We found that men presented a higher smoking prevalence rate, and this was slightly (1.1%) over the national level (52.0%) in 2001 4) . Takemura et al 31) reported a smoking rate of 49.5% in male clerical workers, which was lower than that in transport (64.5%) or production and labor (54.6%) related occupations. A similar finding was observed in the US population, with only 4.9% prevalence (the lowest) for office workers 32) .…”
Section: Discussionmentioning
confidence: 91%
“…The prevalence of H. pylori infection in smokers has been reported as low (Ogihara et al 2000), normal (Brenner et al 1997), or high (Parasher and Eastwood 2000). The influence of smoking on the prevalence of chronic bronchitis has also been little understood (Takemura et al 2005). Therefore, in the present study, we also compared the H. pylori infectious status between the current cigarette smokers and never smokers in patients with chronic bronchitis, showing no impact of cigarette smoking on H. pylori infection.…”
Section: Discussionmentioning
confidence: 83%
“…As the present study was performed under prolonged hypoxic exposure in awake mice, our results may have limited value in explaining the mechanisms of intermittent apnea during sleep in sleep apnea syndrome. However, these findings may be helpful to explain fatal respiratory disturbances observed clinically under hypoxic conditions of various diseases such as chronic obstructive pulmonary disease (Ichinose 2003;Takemura et al 2005) and sleep apnea syndrome (Miki et al 1988;Hida et al 1994;Taguchi et al 1997;Hida 1998).…”
Section: Discussionmentioning
confidence: 99%